2000
DOI: 10.1016/s0006-3495(00)76486-1
|View full text |Cite
|
Sign up to set email alerts
|

A High-Na+ Conduction State during Recovery from Inactivation in the K+ Channel Kv1.5

Abstract: Na(+) conductance through cloned K(+) channels has previously allowed characterization of inactivation and K(+) binding within the pore, and here we have used Na(+) permeation to study recovery from C-type inactivation in human Kv1.5 channels. Replacing K(+) in the solutions with Na(+) allows complete Kv1.5 inactivation and alters the recovery. The inactivated state is nonconducting for K(+) but has a Na(+) conductance of 13% of the open state. During recovery, inactivated channels progress to a higher Na(+) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(80 citation statements)
references
References 35 publications
7
73
0
Order By: Relevance
“…Our experimental data show that inactivation in full-length Kv1.5, as in most voltage-gated K + channels, increases with voltage and eventually stabilizes, so that the inactivation-voltage relationship reaches a basal level at depolarized potentials. In Kv1.5, for very long pulses this is at ∼40% of the maximum current (Fedida et al 1999); although, it should be noted that inactivation can be almost complete when Na + permeates the channel (Wang et al 2000). In Kv1.5ΔN209, inactivation shows a prominent upturn when studied in both HEK 293cells and mouse L cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental data show that inactivation in full-length Kv1.5, as in most voltage-gated K + channels, increases with voltage and eventually stabilizes, so that the inactivation-voltage relationship reaches a basal level at depolarized potentials. In Kv1.5, for very long pulses this is at ∼40% of the maximum current (Fedida et al 1999); although, it should be noted that inactivation can be almost complete when Na + permeates the channel (Wang et al 2000). In Kv1.5ΔN209, inactivation shows a prominent upturn when studied in both HEK 293cells and mouse L cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that substantial Na + can permeate animal Shaker K + channels at very positive potentials; this Na + permeation is often most prominent in the C-type inactivated state of the channels (Callahan and Korn 1994;Kiss et al 1998;Kiss et al 1999;Lopez-Barneo et al 1993;Ogielska and Aldrich 1998;Starkus et al 2000;Starkus et al 1997;Wang et al 2000;Yellen 1998). …”
Section: Cortical Cells Of Rootsmentioning
confidence: 99%
“…Data in Fig. 6A show currents recorded during a 1-s depolarizing pulse to ϩ60 mV from mutant channels in which the arginine at position 487 in the outer pore was replaced with a valine (R487V) [this is equivalent to the T499V mutation in Shaker (Lopez-Barneo et al, 1993;Wang et al, 2000)]. R487V mutant channels showed little inactivation during the pulse, and the effect of 1 M KN-93 was significantly reduced (Fig.…”
Section: Kn-93 Delays Recovery From Inactivation Data Inmentioning
confidence: 99%